Voltammetric determination of uric acid using multiwall carbon nanotubes coated-poly(4-amino-3-hydroxy naphthalene sulfonic acid) modified glassy carbon electrode. Issue 7 (July 2021) - Tefera, Molla; Tessema, Merid; Admassie, Shimelis; Wubet, Walelign
Abstract: In this study, an electrochemical sensor based multiwalled carbon nanotubes (MWCNTs)-poly (4-amino-3-hydroxy naphthalene sulfonic acid) modified glassy carbon electrode (MWCNTs/poly (AHNSA)/GCE) was developed for the determination of uric acid (UA). The composite electrode was prepared first by electropolymerization of the monomer (AHNSA) on GCE using cyclic voltammetry within the potential range of −0.8 V to +2.0 V vs Ag/AgCl for 15 cycles followed by drop coating of MWCNTs solution on the surface of poly (AHNSA)/GCE. Under optimal conditions, MWCNTs/poly (AHNSA)/GCE showed a linear current response with UA concentrations in the range of 1 × 10 −6 to 1 × 10 −4 M with R 2 = 0.9972. The sensor exhibited low detection limit with a value of 0.024 μM. The sensors have been applied to successfully quantify UA in urine samples. Abstract : Uric acid; Multiwalled carbon nanotubes; 4-Amino-3-hydroxy naphthalene sulfonic acid; Urine.